Applying Growth Theory across Countries - Solow, Robert M. (Washington, DC: World Bank, 2014)
The potential problem of reverse causality has been obvious to everyone. It has usually been met with the standard econometric dodge: using lagged values of slow-moving variables as instruments. But this cannot be a serious solution to the problem. The causality issue points to a deeper question: Do cross-country regressions define a meaningful surface along which countries can move back and forth at will? If this is the idea, what mechanism could underlie such a surface? Brock and Durlauf call such a regression a 'model.' Reader suppose in a statistical sense it is. But an economic model should have some internal structure; its causal arrows should rest on some sort of behavioral mechanism, and that seems to be missing in this literature.